2018
DOI: 10.1186/s12885-018-5193-9
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of recombinant MAGE-A3 protein with immunostimulant AS15 in combination with high-dose Interleukin-2 (HDIL2) induction therapy in metastatic melanoma

Abstract: BackgroundHDIL-2 is approved for advanced melanoma based on its durable antitumor activity. MAGE-A3 cancer immunotherapeutic (MAGE-A3 CI) is a recombinant MAGE-A3 protein combined with an immunostimulant adjuvant system and has shown antitumor activity in melanoma. We assessed the safety and anti-tumor activity of HDIL-2 combined with MAGE-A3 CI in advanced melanoma.MethodsPatients with unresectable Stage III or Stage IV MAGE-A3-positive melanoma were enrolled in this phase II study. Treatment included an indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…In addition to the above, several clinical trials using liposomes as carrier system for vaccine have reported safety, capability of inducing prolonged antigen-specific CD4 + and CD8 + T cell responses, as well as prolonged survival in various cancers, including non-small-cell lung carcinoma (NSCLC) ( 166 ), melanoma ( 167 , 168 ), follicular lymphoma ( 169 ) ovarian ( 170 ), breast and prostate cancers ( 171 ).…”
Section: Delivery System As Adjuvantsmentioning
confidence: 99%
“…In addition to the above, several clinical trials using liposomes as carrier system for vaccine have reported safety, capability of inducing prolonged antigen-specific CD4 + and CD8 + T cell responses, as well as prolonged survival in various cancers, including non-small-cell lung carcinoma (NSCLC) ( 166 ), melanoma ( 167 , 168 ), follicular lymphoma ( 169 ) ovarian ( 170 ), breast and prostate cancers ( 171 ).…”
Section: Delivery System As Adjuvantsmentioning
confidence: 99%
“…Some of the nanoparticle vaccines have been evaluated in clinical trials for different cancers (reviewed in [84][85][86]). Among all, liposomes have been used extensively due to their versatility, including Tecemotide™ liposomes [87][88][89], AS15™ lipids [90][91][92], DepoVax™ liposomes [93][94][95], Iscomatrix [96], Cholesteryl pullulan (CHP) nanogels [97], and virus-like nanoparticles [98,99].…”
Section: Nanoparticles In Clinical Trialsmentioning
confidence: 99%
“…Similarly, Anti-CTLA-4 has low level of ORR ( 14 , 15 ). Moreover, the ORR of HDIL-2 monotherapy is 10%–19% with complete ORR of 6%–8% ( 16 ). Therefore, how to improve the ORR of immunotherapy and how to select appropriate indicators to predict the effectiveness of immunotherapy are the two hotspots of current research.…”
Section: Limitations Of Conventional Tumor Immunotherapiesmentioning
confidence: 99%